Fetal Inflammatory Response Syndrome and Cerebral Oxygenation During Immediate Postnatal Transition in Preterm Neonates - Wolfsberger, Christina Helene; Bruckner, Marlies; Baik-Schneditz, Nariae; Schwaberger, Bernhard; Mileder, Lukas Peter; Avian, Alexander; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2020)
Introduction: Fetal inflammatory response syndrome (FIRS), defined as elevated umbilical cord blood interleukin-6 (IL-6) values > 11 pg/ml, is associated with an increased risk of neonatal morbidity and mortality. The primary aim of the present study was to evaluate a potential influence of FIRS on cerebral oxygen saturation (crSO2) and fractional tissue oxygen extraction (cFTOE) during immediate postnatal transition in preterm neonates. The secondary aim was to analyze the potential influence of FIRS on cerebral injury and mortality. Methods: Secondary outcome parameters of prospective observational studies were analyzed. Preterm neonates with measured IL-6 values from umbilical cord blood and cerebral near-infrared spectroscopy (NIRS) measurements during immediate transition after birth were included. Preterm neonates with FIRS (FIRS group) were matched 1:1 for gestational age (± 1 week) to preterm neonates without FIRS (non-FIRS group). crSO2, cFTOE, arterial oxygen saturation (SpO2), heart rate (HR), and fraction of inspired oxygen (FiO2) were compared between both groups. In addition, cerebral injury and mortality were compared between both groups. Results: A total of 46 preterm neonates were included. Twenty-three neonates in the FIRS group [median gestational age 32.1 (IQR 30.3–33.0) weeks; median IL-6 19.7 (IQR 12.2–37.0) pg/ml] were compared to 23 neonates in the non-FIRS group [gestational age: 32.0 (30.4–33.1) weeks; IL-6: 5.4 (3.0–6.7) pg/ml]. cFTOE showed significantly lower values within the first 4 min and a trend toward lower values in minute 5 after birth in the FIRS group. There were no significant differences in crSO2 within the first 15 min after birth between the two groups. SpO2 was significantly lower in minutes 5 and 6 and HR was significantly lower in minutes 2 and 4 after birth in the FIRS group compared to the non-FIRS group. Survival without cerebral injury was similar in both groups. Conclusion: In preterm neonates with FIRS the crSO2 was similar despite significantly lower cFTOE values during the first minutes after birth. This observation may be a result of compromised oxygen consumption and delivery in the first minutes after birth in neonates with FIRS.